Selective Detection of Paraquat in Adulterated and Complex Environmental Samples Using Raman Spectroelectrochemistry - Kavazoi, Henry S. [UNESP]; Miyazaki, Celina M. [UNESP]; Constantino, Carlos J.L. [UNESP]; Martin, Cibely S. [UNESP]; Alessio, Priscila [UNESP] (SAGE Publications, 2024)
Growing demand for pesticides has created an environment prone to deceptive activities, where counterfeit or adulterated pesticide products infiltrate the market, often escaping rapid detection. This situation presents a significant challenge for sensor technology, crucial in identifying authentic pesticides and ensuring agricultural safety practices. Raman spectroscopy emerges as a powerful technique for detecting adulterants. Coupling the electrochemical techniques allows a more specific and selective detection and compound identification. In this study, we evaluate the efficacy of spectroelectrochemical measurements by coupling a potentiostat and Raman spectrograph to identify paraquat, a nonselective herbicide banned in several countries. Our findings demonstrate that applying −0.70 V during measurements yields highly selective Raman spectra, highlighting the primary vibrational bands of paraquat. Moreover, the selective Raman signal of paraquat was discernible in complex samples, including tap water, apple, and green cabbage, even in the presence of other pesticides such as diquat, acephate, and glyphosate. These results underscore the potential of this technique for reliable pesticide detection in diverse and complex matrices.
Keywords: acephate; Counterfeit pesticides; diquat; glyphosate; pesticide mixture; screen-printed electrode